The Encounter Model and Audiological Clinical Encounters - von Hapsburg, Deborah; Tjørnhøj-Thomsen, Tine (Seminars in Hearing, 2012)
The encounter between patient and clinician can often result in a mismatch in perspectives. These differences in perspective may result in differing definitions of hearing loss by the client and clinician and may ultimately lead to unsuccessful outcomes for patients. The Ida Institute has espoused the use of the Encounter Model to help audiologists reflect on the patient perspective, communication partner perspective, and their own perspectives as well. This model is a heuristic that encourages audiologists to reflect on the patients' own characterization, explanation, and ideas about how best to cope with hearing loss in their lives. By better understanding the role of the various personal, professional, and cultural factors that define each patient's unique experience of hearing loss, the audiologist can gain an understanding of the patient's true level of motivation for addressing his or her hearing loss. By using the model to communicate and explore beyond the traditional clinical approach, audiologists can begin to establish more productive relationships with their patients and increase the potential for patient satisfaction and successful outcomes. The Encounter Model also affords clinicians valuable insight that will enable them to reflect on their clinical encounters and adapt their practice to achieve a patient-centered focus.
Keywords: Encounter model; medical anthropology; ethnography